Evaluation of the Injury Control Council of Western Australia's Understanding and Building Resilience in the South West Project Phase 1 - Development of Community Road Maps - McManus, Alexandra; Brown, Graham; Lobo, Roanna (Curtin University of Technology, WA Centre for Health Promotion Research, 2006)
EXECUTIVE SUMMARYThe Understanding and Building Resilience in the South West Project was coordinated by the Injury Control Council of Western Australia (ICCWA) on behalf of the South West Suicide Prevention Taskforce and in partnership with the South West Area Health Service (SWAHS) Population Health Unit. This report was commissioned by ICCWA as an independent evaluation of the process used to develop the Community Road Maps (CRM) and the appropriateness of the recommendations therein to promote understanding of, and build resilience to, suicide in each community involved in the project. The conclusions and recommendations in the report have been developed based on the data collected from key stakeholders in the area of suicide prevention and community members living in the south west of Western Australia.Overall, suicide prevention appears to be an issue of high community concern in the three communities who completed a CRM. Those involved reported that the project was thorough in its consultation and well-managed. The high level of interest in the project was further manifested with a 90% response rate of the evaluation questionnaires and the willingness of participants to engage in follow-up telephone interviews.Small rural communities face significant challenges in providing health services and support to those most in need. Residents often have to travel significant distances to larger towns to access specialist services or training. Furthermore, the stigma associated with suicide and mental illness inhibits some individuals from seeking help earlier rather than later, even when services or assistance is available within their own community.A coordinated and collaborative approach by service providers (both professional and voluntary) would promote a more proactive approach to suicide prevention and serve to maximise the scarce resources available in rural communities. A whole-of-community coordinated approach to the issue of suicide prevention is required to identify and support individuals 'at risk' of suicide, who may not qualify for mental health assistance, but currently appear to fall through the gaps until a crisis point is reached. This evaluation found that strong local leadership was required to drive the project forward, and centrally facilitated processes and frameworks were considered essential to implement the recommendations provided in each Community Road Map.